Equity and justice in heat planning across small, midsize, and large cities in the US - Xiaofei Qin; Abigail Sullivan; Anne G. Short Gianotti (Landscape and Urban Planning, 2026)

Design with nonhumans takes wildlife agency into account to reduce conflicts - Meredith Root‐Bernstein; Anne G. Short Gianotti (Conservation Biology, 2026)
The concept of nonhuman animal agency has recently been introduced in fields from more‐than‐human geography to wildlife conservation. Nonhuman animal agency refers to the capacity of animals to create, set in motion, and cause or influence actions through their relations with humans and other nonhumans. Ecologists have long recognized that animal species are active components of ecosystems and have important ecological functions, yet most wildlife management treats species as objects that are (or should be) passive and controllable. We argue that explicit recognition of nonhuman agency can reduce human–wildlife conflict, enhance the capacity for coexistence, and create better outcomes for conservation and other human‐based projects. Rather than attempting to control species, the emerging more‐than‐human perspective suggests that a better target of management is place‐based relationships, where humans and a variety of nonhumans are active participants in shaping landscape structures and lived experiences. To implement this concept in practice, we present design with nonhuman species as a pragmatic approach that draws on and may combine elements of contemporary design methods, coexistence approaches, rewilding perspectives, adaptive management, and traditional land management practices. The uniqueness of this approach is its focus on responding to both human and nonhuman agencies and its interactive problem solving mediated by materials, objects, structures, spaces, and spatiotemporal patterns. Design with seeks to appreciate and embody desires and concepts, which can be understood as being held by both humans and nonhumans. Critically, design with enables forms of negotiation that are not based on impractical anthropocentric linguistic and political models. We encourage conservationists to engage with designers interested in design with nonhumans.

Continental shelf evolution on a passive continental margin, southeast New South Wales, Australia - B. G. Thom; P. J. Cowell; J. P. Hudson; M. A. Kinsela; A. D. Short (Australian Journal of Earth Sciences, 2026)

A reproductive and trophic analysis of corals in a degraded environment - Morgan L. Short; Hilary G. Close; David S. Gilliam; Joana Figueiredo (Coral Reefs, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Induced sexual reproduction ex situ reveals bidirectional sex change of the coral Montastraea cavernosa - Krista V. Laforest; Chelsea G. Petrik; Ashlee A. Hylton; Rachel L. Ionata; E. Murphy McDonald; Morgan L. Short; Joana Figueiredo (Coral Reefs, 2024)

The added value of simulated near-surface wind speed over the Alps from a km-scale multimodel ensemble - M. O. Molina; J. M. Careto; C. Gutiérrez; E. Sánchez; K. Goergen; S. Sobolowski; E. Coppola; E. Pichelli; N. Ban; D. Belus̆ić; C. Short; C. Caillaud; et al. (Climate Dynamics, 2024)
The advancement of computational resources has allowed researchers to run convection-permitting regional climate model (CPRCM) simulations. A pioneering effort promoting a multimodel ensemble of such simulations is the CORDEX Flagship Pilot Studies (FPS) on “Convective Phenomena over Europe and the Mediterranean” over an extended Alps region. In this study, the Distribution Added Value metric is used to determine the improvement of the representation of all available FPS hindcast simulations for the daily mean near-surface wind speed. The analysis is performed on normalized empirical probability distributions and considers station observation data as the reference. The use of a normalized metric allows for spatial comparison among the different regions (coast and inland), altitudes and seasons. This approach permits a direct assessment of the added value between the CPRCM simulations against their global driving reanalysis (ERA-Interim) and respective coarser resolution regional model counterparts. In general, the results show that CPRCMs add value to their global driving reanalysis or forcing regional model, due to better-resolved topography or through better representation of ocean-land contrasts. However, the nature and magnitude of the improvement in the wind speed representation vary depending on the model, the season, the altitude, or the region. Among seasons, the improvement is usually larger in summer than winter. CPRCMs generally display gains at low and medium-range altitudes. In addition, despite some shortcomings in comparison to ERA-Interim, which can be attributed to the assimilation of wind observations on the coast, the CPRCMs outperform the coarser regional climate models, both along the coast and inland.

Multiple social and environmental factors affect wildland fire response of full or less-than-full suppression - Molly C. Daniels; Kristin H. Braziunas; Monica G. Turner; Ting-Fung Ma; Karen C. Short; Adena R. Rissman (Journal of Environmental Management, 2024)

An analogous scale model for laboratory mixing studies - J. Wu; L. Graham; S. Peacock; B. Nguyen; Y. Feng; M. Hurley; G. Short; D. Harris; W. Bruckard (Minerals Engineering, 2023)

Evaluation framework for Techno-economic analysis of energy system retrofit technologies - Tariq G. Ahmed; Bjarnhedinn Gudlaugsson; Chris Ogwumike; Huda Dawood; Michael Short; Nashwan Dawood (Energy and Buildings, 2023)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Smoke from simulated forest fire alters secondary metabolites in Vitis vinifera L. berries and wine - Matthew Noestheden; Benjamin Noyovitz; Seamus Riordan-Short; Eric G. Dennis; Wesley F. Zandberg (Planta, 2018)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Cortical neural arousal is differentially affected by type of physical exercise performed - Nicholas J. Hanson; Lindsey E. Short; Lauren T. Flood; Nicholas P. Cherup; Michael G. Miller (Experimental Brain Research, 2018)

Zebrafish as a useful model for immunological research with potential applications in aquaculture - Manuel Lee‐Estevez; Elías Figueroa; Jacky Cosson; Stefanía E. Short; Ivan Valdebenito; Patricio Ulloa‐Rodríguez; Jorge G. Farías (Reviews in Aquaculture, 2018)
The Zebrafish ( Danio Rerio ) is a Teleost fish, which offers several practical advantages concerning manipulation, maintenance and versatility as well as short life cycle, low cost and physiological similarity with most farmed species. Zebrafish have been used as model for several aquaculture‐relevant infectious agents, since the cost of infections to aquaculture can be great, making failure of immunity a major risk for commercial fish farming. This have allowed scientist to understand pathogens biology as well as fish immune response against infection, and thus have helped to improve disease control in aquaculture. This review summarizes the recent reports and main knowledge concerning the cellular and molecular aspects of the immune response in zebrafish and its potential applications in the fish farming industry. Several research results in zebrafish and other teleosts reveal that mucosal tissues have a strong and well‐structured immune response involving both innate and adaptive components. Together with the advantages of low maintenance cost, easy handling and genetic tools available, zebrafish comes up as a useful and reliable animal model for in vivo study of fish immune response and mechanisms as well as fish‐affecting infectious and inflammatory diseases which are a cause of concern for the aquaculture industry. Also, vaccines development, drugs screening and immunologically focused fish food assessment seem to be promising fields where zebrafish model can be used to generate positive impacts to the aquaculture practice.

Verticillium dahliae manipulates plant immunity by glycoside hydrolase 12 proteins in conjunction with carbohydrate‐binding module 1 - Yue‐Jing Gui; Jie‐Yin Chen; Dan‐Dan Zhang; Nan‐Yang Li; Ting‐Gang Li; Wen‐Qi Zhang; Xin‐Yan Wang; Dylan P. G. Short; Lei Li; Wei Guo; Zhi‐Qiang Kong; Yu‐Ming Bao; et al. (Environmental Microbiology, 2017)
Summary Glycoside hydrolase 12 (GH12) proteins act as virulence factors and pathogen‐associated molecular patterns (PAMPs) in oomycetes. However, the pathogenic mechanisms of fungal GH12 proteins have not been characterized. In this study, we demonstrated that two of the six GH12 proteins produced by the fungus Verticillium dahliae Vd991, VdEG1 and VdEG3 acted as PAMPs to trigger cell death and PAMP‐triggered immunity (PTI) independent of their enzymatic activity in Nicotiana benthamiana . A 63‐amino‐acid peptide of VdEG3 was sufficient for cell death‐inducing activity, but this was not the case for the corresponding peptide of VdEG1. Further study indicated that VdEG1 and VdEG3 trigger PTI in different ways: BAK1 is required for VdEG1‐ and VdEG3‐triggered immunity, while SOBIR1 is specifically required for VdEG1‐triggered immunity in N. benthamiana . Unlike oomycetes, which employ RXLR effectors to suppress host immunity, a carbohydrate‐binding module family 1 (CBM1) protein domain suppressed GH12 protein‐induced cell death. Furthermore, during infection of N. benthamiana and cotton, VdEG1 and VdEG3 acted as PAMPs and virulence factors, respectively indicative of host‐dependent molecular functions. These results suggest that VdEG1 and VdEG3 associate differently with BAK1 and SOBIR1 receptor‐like kinases to trigger immunity in N. benthamiana , and together with CBM1‐containing proteins manipulate plant immunity.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Defining urban, suburban, and rural: a method to link perceptual definitions with geospatial measures of urbanization in central and eastern Massachusetts - Anne G. Short Gianotti; Jackie M. Getson; Lucy R. Hutyra; David B. Kittredge (Urban Ecosystems, 2016)

Globally invading populations of the fungal plant pathogen V erticillium dahliae are dominated by multiple divergent lineages - Dylan P. G. Short; Suraj Gurung; Pierre Gladieux; Patrik Inderbitzin; Zahi K. Atallah; Franco Nigro; Guoqing Li; Seher Benlioglu; Krishna V. Subbarao (Environmental Microbiology, 2015)
Summary The spread of aggressive fungal pathogens into previously non‐endemic regions is a major threat to plant health and food security. Analyses of the spatial and genetic structure of plant pathogens offer valuable insights into their origin, dispersal mechanisms and evolution, and have been useful to develop successful disease management strategies. Here, we elucidated the genetic diversity, population structure and demographic history of worldwide invasion of the ascomycete V erticillium dahliae , a soil‐borne pathogen, using a global collection of 1100 isolates from multiple plant hosts and countries. Seven well‐differentiated genetic clusters were revealed through discriminant analysis of principal components ( DAPC ), but no strong associations between these clusters and host/geographic origin of isolates were found. Analyses of clonal evolutionary relationships among multilocus genotypes with the e BURST algorithm and analyses of genetic distances revealed that genetic clusters represented several ancient evolutionary lineages with broad geographic distribution and wide host range. Comparison of different scenarios of demographic history using approximate B ayesian computations revealed the branching order among the different genetic clusters and lineages. The different lineages may represent incipient species, and this raises questions with respect to their evolutionary origin and the factors allowing their maintenance in the same areas and same hosts without evidence of admixture between them. Based on the above findings and the biology of V . dahliae , we conclude that anthropogenic movement has played an important role in spreading V . dahliae lineages. Our findings have implications for the development of management strategies such as quarantine measures and crop resistance breeding.

Characterising the distribution of near-shore submarine groundwater discharge along a coastline using 222 Rn and electrical conductivity - M. A. Short; S. Lamontagne; P. G. Cook; R. Cranswick (Australian Journal of Earth Sciences, 2014)

Governing Change: Land-Use Change and the Prevention of Nonpoint Source Pollution in the North Coastal Basin of California - Anne G. Short (Environmental Management, 2013)

Why replication is important in landscape genetics: American black bear in the Rocky Mountains - R. A. SHORT BULL; S. A. CUSHMAN; R. MACE; T. CHILTON; K. C. KENDALL; E. L. LANDGUTH; M.K. SCHWARTZ; K. MCKELVEY; FRED W. ALLENDORF; G. LUIKART (Molecular Ecology, 2011)
We investigated how landscape features influence gene flow of black bears by testing the relative support for 36 alternative landscape resistance hypotheses, including isolation by distance (IBD) in each of 12 study areas in the north central U.S. Rocky Mountains. The study areas all contained the same basic elements, but differed in extent of forest fragmentation, altitude, variation in elevation and road coverage. In all but one of the study areas, isolation by landscape resistance was more supported than IBD suggesting gene flow is likely influenced by elevation, forest cover, and roads. However, the landscape features influencing gene flow varied among study areas. Using subsets of loci usually gave models with the very similar landscape features influencing gene flow as with all loci, suggesting the landscape features influencing gene flow were correctly identified. To test if the cause of the variability of supported landscape features in study areas resulted from landscape differences among study areas, we conducted a limiting factor analysis. We found that features were supported in landscape models only when the features were highly variable. This is perhaps not surprising but suggests an important cautionary note – that if landscape features are not found to influence gene flow, researchers should not automatically conclude that the features are unimportant to the species’ movement and gene flow. Failure to investigate multiple study areas that have a range of variability in landscape features could cause misleading inferences about which landscape features generally limit gene flow. This could lead to potentially erroneous identification of corridors and barriers if models are transferred between areas with different landscape characteristics.

Estuarine shoreline processes in a dynamic low-energy system - Ana Vila-Concejo; Michael G. Hughes; Andrew D. Short; Roshanka Ranasinghe (Ocean Dynamics, 2010)

Pain Assessment in Animals - A. Bufalari; C. Adami; G. Angeli; C. E. Short (Veterinary Research Communications, 2007)

The transport and mass balance of fallout radionuclides in Blelham Tarn, Cumbria (UK) - P.G. Appleby; E.Y. Haworth; H. Michel; D.B. Short; G. Laptev; G.T. Piliposian (Journal of Paleolimnology, 2003)